Teachers' Challenges and Strategies in Teaching Speaking Through a Screen - Yolanda Putri; Fazri Nur Yusuf (Universitas Islam Negeri Walisongo Semarang, 2025)
Online learning has become a common way to deliver instruction, particularly in hybrid educational models. However, teaching speaking skills presents unique challenges because it requires real-time interaction, pronunciation practice, and fluency development. This study investigates the challenges senior high school English teachers face when teaching speaking online, the strategies they employ, and the support they require. Using a qualitative approach, data were collected from 20 teachers through questionnaires and in-depth interviews with four of them. Thematic analysis revealed four main challenges: low student engagement, time constraints that hindered feedback on pronunciation and accuracy, limited resources for authentic speaking tasks, and technical difficulties that disrupted fluency and real-time communication. To address these issues, teachers implemented various strategies. Group discussions encouraged interaction and confidence; presentations supported fluency, vocabulary, and idea organization; role-plays helped reduce anxiety and provided opportunities to practice pronunciation in contextual settings; and debates enhanced fluency, reasoning, and spontaneous speaking. The teachers also emphasized the need for engaging teaching materials, technology training, and collaborative professional development. The study concludes that although online speaking instruction presents significant challenges, strategies combined with institutional support can foster students’ fluency, accuracy, pronunciation, vocabulary, intonation, and comprehension. It is recommended that schools provide engaging digital materials, targeted teacher training, and reliable infrastructure to enhance the effectiveness of online speaking instruction.